If F ( x , y ) = x 2 + y 2 − y i + x 2 + y 2 x j is a vector field and C is a positively oriented, piecewise smooth simple closed curve enclosing the origin, then the line integral ∮ C F ⋅ d r =
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used Amperes circuital Law. Notice , this field is anagalous to magnetic field due to an infinite wire passing through origin along z axis . Comparing with the magnetic field and applying amperes law directly gives the answer.
Consider a smooth simple closed curve C in R 2 that does not run through the origin. Let's parameterize this curve, s ( t ) , with 0 ≤ t ≤ 1 . We can write this parameterization in terms of polar coordinates, x = r ( t ) cos ( θ ( t ) ) , y = r ( t ) sin ( θ ( t ) ) , where the phase angle θ is measured continuously along the curve, of course. A straightforward if slightly tedious computation shows that ∫ C x 2 + y 2 − y d x + x 2 + y 2 x d y = θ ( 1 ) − θ ( 0 ) , the change of θ along the way. Since s ( 1 ) = s ( 0 ) for a closed curve, these two polar angles will differ by a multiple of 2 π ,showing that ∮ C F ⋅ d s is an integer multiple of 2 π . If the curve is simple and running in the counterclockwise direction around the origin, then the line integral must be 2 π .
Problem Loading...
Note Loading...
Set Loading...
Let C be a positively oriented piecewise smooth simple closed curve enclosing the origin, and choose a sufficiently small radius a so that the circle C ’ given by x 2 + y 2 = a 2 is contained in C . Parametrize C ’ by r ( t ) = ⟨ a cos t , a sin t ⟩ , 0 ≤ t ≤ 2 π . Let C ’ ′ = C ∪ ( − C ’ ) and let D be the region between C and C ’ . By Green’s Theorem,
∮ C ’ ′ F ⋅ d r = ∮ C ’ ′ P ( x , y ) d x + Q ( x , y ) d y = ∬ D ( ∂ x ∂ Q − ∂ y ∂ P ) d A
where P ( x , y ) = x 2 + y 2 − y and Q ( x , y ) = x 2 + y 2 x Since ∂ x ∂ Q − ∂ y ∂ P = 0 ,
∮ C ’ ′ P d x + Q d y = ∮ C ∪ ( − C ’ ) P d x + Q d y = ∮ C P d x + Q d y − ∮ C ’ P d x + Q d y = 0 so that ∮ C P d x + Q d y = ∮ C ’ P d x + Q d y
∮ C ’ P d x + Q d y = ∫ 0 2 π a 2 cos 2 ( t ) + a 2 sin 2 ( t ) − a sin t ( − a sin t ) d t + a 2 cos 2 ( t ) + a 2 sin 2 ( t ) a cos t ( a cos t ) d t = ∫ 0 2 π d t = 2 π